2017
DOI: 10.4236/jtr.2017.54029
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Mortality among Multidrug Resistant Tuberculosis MDR/RR-TB Patients in Democratic Republic of Congo

Abstract: Background: Tuberculosis remains a very common infectious disease in Democratic Republic of Congo (DRC). The resistance to drugs worsens the prognosis and the outcome of patients affected tuberculosis and increase their mortality. Objective: To identify factors associated with death among Multidrugs resistant tuberculosis (MDR/RR TB) patients referred to the referential hospital, Centre d'Excellence Damien (CEDA). Materials and Methods: A retrospective cohort study of patients attending health care to the Cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…In the current study, about 15.13% of patients with MDR/RR-TB died during their anti-TB treatment follow-up. Comparable mortality rates were also reported from different countries; Pakistan (Javaid et al, 2018;Khan et al, 2015), South Africa (Hirasen et al, 2018), Democratic Republic of Congo (Kashongwe et al, 2017), Tajikistan (Makhmudova et al, 2019), Malaysia (Mohd Shariff et al, 2016, India (Nair et al, 2017) and Taiwan (Lin et al, 2019). Relatively lower mortality rates were reported from Kenya (Kiprotich et al, 2014), Sudan (Ali et al, 2019), Egypt (Gadallah et al, 2016), Brazil (Gayoso et al, 2018), USA (Kurbatova et al, 2012), Lativa (Leimane et al, 2005), Tanzania (Mollel and Chilongola, 2017), and China (Zhang et al, 2018).…”
Section: Discussionmentioning
confidence: 70%
“…In the current study, about 15.13% of patients with MDR/RR-TB died during their anti-TB treatment follow-up. Comparable mortality rates were also reported from different countries; Pakistan (Javaid et al, 2018;Khan et al, 2015), South Africa (Hirasen et al, 2018), Democratic Republic of Congo (Kashongwe et al, 2017), Tajikistan (Makhmudova et al, 2019), Malaysia (Mohd Shariff et al, 2016, India (Nair et al, 2017) and Taiwan (Lin et al, 2019). Relatively lower mortality rates were reported from Kenya (Kiprotich et al, 2014), Sudan (Ali et al, 2019), Egypt (Gadallah et al, 2016), Brazil (Gayoso et al, 2018), USA (Kurbatova et al, 2012), Lativa (Leimane et al, 2005), Tanzania (Mollel and Chilongola, 2017), and China (Zhang et al, 2018).…”
Section: Discussionmentioning
confidence: 70%
“…From among the 43 studies that were included, a total of 31,525 persons receiving SLD were followed-up and 4,976 of them encountered the incidence of mortality. The study participants for four of these studies were children [32][33][34][35]; for 20 of the studies were adults [23,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54]; and for 19 of the studies were both adults and children [55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73]. Methodological design for nine of the studies was prospective cohort [23, 39, 42-46, 50, 63] while it was retrospective cohort for 34 of the remaining studies [32-38, 40, 41, 47-49, 51-62, 64-73].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…from the central region [42,64]; one of the study was from the western region [59]; and the remaining one study was from multi-sites in different SSA regions [50]. A total of 23 studies out of the 43 publications identified had reported the predictors of mortality among the persons receiving SLD therapy [23, 32, 34, 35, 37-41, 44, 47, 49, 52, 54, 55, 57, 59-61, 64, 67, 69, 71].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, authors have also found that most TB related deaths in PLHIV were within the first 3 months of diagnosis of HIV [12]. Drug resistance is another important factor contributing to mortality in HIV‐TB co‐infected patients [13, 14]. It has been reported that 1 month and 1 year mortality was higher in those with drug resistance, and mortality increased with the degree of resistance (higher in extensive drug resistance [XDR] compared with multidrug resistant [MDR]) [15].…”
Section: Introductionmentioning
confidence: 99%